Maybe someday : a novel - Hoover, Colleen (New York : Atria PaperBack, 2014)
When she discovers that her boyfriend is cheating on her, Sydney, a 22-year-old college student, must decide what to do next, especially when she becomes captivated by her mysterious neighbor Ridge.
Keywords: Betrayal -- Fiction; College students -- Fiction; Friendship -- Fiction